The Sociology of Community Connections - Bruhn, John G. author. aut Link
XXIII, 328 p.
Keywords: Many of our current social problems have been attributed to the breakdown or loss of community as a place and to the fragmentation of connections due to an extreme value of individualism in the Western world, particularly in the United States. Not all scholars and researchers agree that individualism and technology are the primary culprits in the loss of community as it existed in the middle decade of the 20th century. Nonetheless, people exist in groups, and connections are vital to their existence and in the daily performance of activities. The second edition of the Sociology of Community Connections will identify and help students understand community connectedness in the present and future.